The five Ps of LD in practice: student partnership approaches in one-to-one, workshops and online work - Helen Michelle Webster (Journal of Learning Development in Higher Education)
Learning Development espouses values that promote tailored, holistic, empowering, emancipatory, non-judgemental and student-centred practice. However, it is harder to imagine what these values look like as concrete principles in the context of our work, so we can ensure that we are consciously and deliberately enacting them. The Five Ps of LD (Webster, 2023) were developed as a framework to embed the principle of ‘formulation’ into LD practice. Formulation is a partnership approach, borrowed from counselling and psychology, in which the student and the LDer work together as equals to explore academic skills issues holistically and identify suitable ways forward in the context of the student’s own lived experience, rather than a hierarchical, directive one in which the LDer diagnoses and prescribes guidance to the passive student. It also offers a way to turn Academic Literacies (Lea and Street, 1998) from an abstract theory to a pedagogy and a praxis.